Perinatal exposure to low-dose methoxychlor impairs testicular development in C57BL/6 mice. - Xiaohong Du (Public Library of Science (PLoS), 2014)
Methoxychlor (MXC), an organochlorine pesticide, has adverse effects on male reproduction at toxicological doses. Humans and wild animals are exposed to MXC mostly through contaminated dietary intake. Higher concentrations of MXC have been found in human milk, raising the demand for the risk assessment of offspring after maternal exposure to low doses of MXC. In this study, pregnant mice (F0) were given intraperitoneal daily evening injections of 1 mg/kg/d MXC during their gestational (embryonic day 0.5, E0.5) and lactational periods (postnatal day 21.5, P21.5), and the F1 males were assessed. F1 testes were collected at P0.5, P21.5 and P45.5. Maternal exposure to MXC disturbed the testicular development. Serum testosterone levels decreased, whereas estradiol levels increased. To understand the molecular mechanisms of exposure to MXC in male reproduction, the F1 testes were examined for changes in the expression of steroidogenesis- and spermatogenesis- related genes. RT-PCR analysis demonstrated that MXC significantly decreased Cyp11a1 and increased Cyp19a1; furthermore, it downregulated certain spermatogenic genes (Dazl, Boll, Rarg, Stra8 and Cyclin-a1). In summary, perinatal exposure to low-dose MXC disturbs the testicular development in mice. This animal study of exposure to low-dose MXC in F1 males suggests similar dysfunctional effects on male reproduction in humans.